COUNSELLING APPROACHES FOR ADDRESSING ETHICAL DILEMMAS IN ADOLESCENTS - MAIKAMBA, Abubakar, M.; BIBI, Meshak; ABUBAKAR, Muhammad, K.; MUHAMMAD, Aishatu, N. (Journal of Professional Counselling, 2025)
Adolescents often face ethical dilemmas that can have profound effects on their development and well-being. This paper explores various counselling approaches that can be employed to address these dilemmas. By examining theoretical frameworks and practical interventions, this paper aims to provide counselors with effective strategies for helping adolescents navigate ethical challenges. Key approaches discussed include cognitive-behavioral therapy, narrative therapy, and solution-focused therapy. The paper also considers the role of cultural competence and the integration of ethical decision-making models in counselling practices